Threat Intelligence Sharing: Analyzing Strategies and Challenges in Sharing Threat Intelligence Among Organizations to Enhance Cybersecurity Posture and Incident Response (Cybersecurity and Network Defense Research, 2024)
Threat intelligence sharing plays a crucial role in enhancing cybersecurity posture and incident response capabilities. This paper provides an in-depth analysis of the strategies and challenges associated with sharing threat intelligence among organizations. The study examines various approaches to threat intelligence sharing, including information sharing and analysis centers (ISACs), public-private partnerships, and industry collaboration initiatives. The paper also explores the benefits of threat intelligence sharing, such as improved situational awareness, faster incident response, and enhanced defense against cyber threats. However, several challenges hinder effective threat intelligence sharing, including trust issues, legal and regulatory concerns, and technical interoperability issues. The paper concludes with recommendations for addressing these challenges and enhancing the effectiveness of threat intelligence sharing efforts.